A glance at subgenomic flavivirus RNAs and microRNAs in flavivirus infections. Issue 1 (December 2016) - Bavia, Lorena; Mosimann, Ana; Aoki, Mateus; Duarte dos Santos, Claudia
Abstract The familyFlaviviridae comprises a wide variety of viruses that are distributed worldwide, some of which are associated with high rates of morbidity and mortality. There are neither vaccines nor antivirals for most flavivirus infections, reinforcing the importance of research on different aspects of the viral life cycle. During infection, cytoplasmic accumulation of RNA fragments mainly originating from the 3′ UTRs, which have been designated subgenomic flavivirus RNAs (sfRNAs), has been detected. It has been shown that eukaryotic exoribonucleases are involved in viral sfRNA production. Additionally, viral and human small RNAs (sRNAs) have also been found in flavivirus-infected cells, especially microRNAs (miRNAs). miRNAs were first described in eukaryotic cells and in a mature and functional state present as single-stranded 18–24 nt RNA fragments. Their main function is the repression of translation through base pairing with cellular mRNAs, besides other functions, such as mRNA degradation. Canonical miRNA biogenesis involves Drosha and Dicer, however miRNA can also be generated by alternative pathways. In the case of flaviviruses, alternative pathways have been suggested. Both sfRNAs and miRNAs are involved in viral infection and host cell response modulation, representing interesting targets of antiviral strategies. In this review, we focus on the generation and function of viral sfRNAs, sRNAs and miRNAs in West Nile, dengue, Japanese encephalitis, Murray Valley encephalitis and yellow fever infections, as well as their roles in viral replication, translation and cell immune response evasion. We also give an overview regarding other flaviviruses and the generation of cellular miRNAs during infection.